2001
DOI: 10.1093/nar/29.5.1061
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human DNA helicase V with the far upstream element-binding protein

Abstract: The properties of human DNA helicase V (HDH V) were studied in greater detail following an improved purification procedure. From 450 g of cultured cells, <0.1 mg of pure protein was isolated. HDH V unwinds DNA unidirectionally by moving in the 3' to 5' direction along the bound strand in an ATP- and Mg(2+)-dependent fashion. The enzyme is not processive and can also unwind partial RNA-RNA duplexes such as HDH IV and HDH VIII. The M:(r) determined by SDS-PAGE (66 kDa) corresponds to that measured under native c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…c-MYC expression (31,32). Its direct and specific binding to RNA2 ⌬1 was confirmed by immunoblotting analyses following RNA affinity chromatography of RNA2 ⌬1 and ⌬3 in nuclear extracts of normal and damage-treated cells (Fig.…”
Section: Mass Spectrometric Identification Of Differentially Bound Prmentioning
confidence: 70%
See 2 more Smart Citations
“…c-MYC expression (31,32). Its direct and specific binding to RNA2 ⌬1 was confirmed by immunoblotting analyses following RNA affinity chromatography of RNA2 ⌬1 and ⌬3 in nuclear extracts of normal and damage-treated cells (Fig.…”
Section: Mass Spectrometric Identification Of Differentially Bound Prmentioning
confidence: 70%
“…FUBP1 is single strand DNA and RNA-binding protein best known for its role as a transcriptional regulator of the proto-oncogene c-MYC in many cancer types (31,32,50,51) and also as regulator of post-transcriptional events such as translation (38) and mRNA stability (23). However, despite the fact that FUBP1 has been isolated in association with spliceosomal complexes (40) and includes four K homology domains (domains homologous to heterogeneous nuclear ribonucleoprotein K, a component of the spliceosomal H complexes (52)), its role in splicing regulation has remained speculative until recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not obvious how these various activities are related or whether they need to be. However, sequencing of peptides derived from purified human DNA helicase V revealed that it is FBP; notably, this protein preparation also worked as an RNA helicase (Vindigni et al, 2001). If FBP or any of its homologs are truly RNA helicases, it may be that the protein is involved in the assembly or remodeling of RNP complexes on mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…TFIIH is necessary for various steps during transcription open-complex formation, initiation and promoter clearance. By recruiting TFIIH, FBP may control the diverse inputs of other transcription factors into basal transcription machinery (Vindigni et al, 2001).…”
Section: Introductionmentioning
confidence: 99%